A comparative anatomical, histological and histochemical study of small intestine in Kestrel (Falco tunniculus) and white eared bulbul (Picnonotic leucotis) according to their food type: Ahmed S. AL-A´araji and Siraj Moner AL-Kafagy - AL-A´araji, Ahmed S. (The Iraqi Journal of Veterinary Medicine, 2017)
This study was conducted on 30 birds (15 birds for each type) divided as 10 birds for each part of study. Anatomical part revealed that the small intestine in both birds kestrel (Falco tinniculus) and white eared bulbul (Picnonotic leucotis) formed from 3 segments; duodenum, jejunum and ileum with no clear demarcation line between them. In kestrel the Meckel's diverticulum appeared as small projection to separate between jejunum and ileum. Both ratio of intestinal length to body length and of intestinal weight to body weight was higher in bulbul than those in kestrel. Histological study showed that the wall of all three parts of small intestine was composed of the same histological layers; these are mucosa, submucosa, muscularis and serosa. There was almost similarity in structure of these tunics but significant differences in several Histomorphometric measurements of each tunica. Goblet cells were more abundant in all parts of small intestine of bulbul than those in kestrel and there was a gradual increasing in the number of these cells toward the end of intestine of both birds. Histochemical part of this study appeared that in villi and crypts of all small intestinal segments of both birds the goblet cells secrete neutral mucin in nature because it showed negative reaction to Alcian blue stain and positive to PAS stain.